On the political commitment of art (and artists) in Pobr e gente de P arís by Sebastián Salazar Bondy - Mudarra Montoya, Américo (2017)
From our perspective, the text Pobre gente de París is a poetic-political manifesto. In it, our author tries to agree on the vision of the literary writer and the vision of the political activist. The book is not, therefore, a mere set of “Parisian experiences” related by its condition of “autobiographical material”. Rather, it is a vehicle of ideas, which will continue along the same route that had formed their articles of opinion in the written press of those years. Then, we can observe that the ideas of Salazar Bondy run without difficulty between the lines of the text Pobre gente de París. The condemnation dictated in the page of a newspaper appears again in the pages of this book, perhaps in other words, perhaps with different extension, but always with the same indignation, with the same anger.